Respiratory Syncytial Virus Outbreak in Infants and Young Children during COVID-19 Pandemic in Taiwan - Hsin Chi; Ching-Hu Chung (MDPI AG, 2023)
Respiratory syncytial virus (RSV) is a major burden of disease in babies and young children, including hospitalizations and deaths. RSV is a seasonal disease that peaks when temperatures decrease in temperate zones and humidity increases in tropical regions. Existing research reveals that RSV hospitalization activity is year-round in Taiwan, which is a subtropical region with small peaks in spring and fall. The monthly distribution and COVID-19 pandemic impact were unclear. The aim of this study was to investigate Taiwan's RSV hospitalization seasonality and the COVID-19 pandemic effects. The National Health Insurance Database and Death Registration Files from the Center for Health and Welfare Data Science Center were connected to birth data for this study. RSV hospitalization (RSVH) in infants aged 0-1 years ranged from 0.9518% (2009) to 1.7113% (2020), substantially higher than in children aged 1-5. Most years had 2 or 3 RSV epidemic seasons in 0-5-year-olds over the 13-year follow-up. RSVH incidence was low until the autumn of 2020, when a major rise occurred after September and lasted until December 2020. We detected RSVH peaks in February-May and July-August. The 2020 RSV outbreak was found at the end of 2020.